Midwives\' Satisfaction with family physician plan in Rasht - K Ghorbani; H Najaf Zadeh; A Sedighi; SM Mousavi; MH Mahdavi; F Monajemi (Guilan University of Medical Sciences, 2014)
Introduction: Job satisfaction reflects a favorable institutional atmosphere in any organization. Job satisfaction causes attraction, survival and employers job motivation. It is important to note job satisfaction of midwives as a key component of health system for promoting mother and children health care processes. Objective : This study was designed and implemented to determine the satisfaction of midwives in family physician program. Methods : In this descriptive cross sectional study, 42 midwives employed in Rasht health center were selected by census in 2008. Data collection instrument was a researcher made questionnaire based on Smith JDI including two parts covering socio-demographical and 26 items on workplace environmental factors, management aspects, education and welfare aspects and job time structure. Descriptive and inferential tests such as Chi-Square , U Mann Whiteny and Spearman were used for data analysis. Results: The mean of midwives' job experience was 3.6 ± 1.5. Least satisfaction in job welfare aspect obtained 44% of satisfaction score and highest satisfaction in job managing aspects received mean score of 70%. There was no correlation between marries and job satisfaction except in job welfare aspect where that singles were more satisfaction (p<0.05). Conclusion : In assessment of midwives' satisfaction, it is shown that job does not exist in welfare aspect. In attention to the fact that lack of satisfaction can affect the quality of health care, it is necessary to reconsider midwives' payment and decrease their work hours.